2013
DOI: 10.1089/neu.2013.2938
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Developing Common Data Elements for Traumatic Brain Injury Research: Version Two – The End of the Beginning

Abstract: To accelerate data sharing and research on traumatic brain injury (TBI), several federal agencies have been collaborating to support the development and implementation of common data elements (CDEs). The first recommendations for CDEs were made in 2010, and were well suited for hospital-based studies of acute TBI in adults. To broaden the utility of the TBI CDEs, experts were asked to update the recommendations to make them relevant to all ages, levels of injury severity, and phases of recovery. The second ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 22 publications
0
120
0
Order By: Relevance
“…Version 2 of the CDE specified the most appropriate outcome measures according to severity of TBI, age of the patient and phase of recovery 95 . The National Institute of Neurological Disorders and Stroke (NINDS) designated the GOSE as a 'core' CDE measure of global outcome of adult TBI, including outcomes of acute hospitalization, rehabilitation after moderate to severe head injury, mild TBI, and as an outcome measure in epidemiology studies.…”
Section: [H1] International Developmentsmentioning
confidence: 99%
“…Version 2 of the CDE specified the most appropriate outcome measures according to severity of TBI, age of the patient and phase of recovery 95 . The National Institute of Neurological Disorders and Stroke (NINDS) designated the GOSE as a 'core' CDE measure of global outcome of adult TBI, including outcomes of acute hospitalization, rehabilitation after moderate to severe head injury, mild TBI, and as an outcome measure in epidemiology studies.…”
Section: [H1] International Developmentsmentioning
confidence: 99%
“…Specific criteria for determining which item was most important were not given. ) and in other populations, such as traumatic brain injury, 9 these do not adequately address rehabilitation domains 10 or sufficiently detail rehabilitation research and practice needs.…”
Section: Focus Groupsmentioning
confidence: 99%
“…To date, a literature search was conducted to identify peer-reviewed literature on the effect of exercise therapy on walking for persons with MS. The research question is whether the effects identified priorities are 1) ensuring that high-quality data standards are met by having a scientific advisory board [5][6][7][8] advise on policy and procedures and oversee data use requests and implementing a strong data validation system; 2) creating data uniformity with common data elements, 9,10 a core set of measures, 10,24 and standardized collection protocols for prospective data sharing; 3) using a secure and user-friendly interface that minimizes the time commitment, such as iMED (Merck Serono SA, Geneva, Switzerland) 5 ; and 5) addressing ownership and acknowledgment rights for data contributors and rules for authorship of aggregated analyses through the use of data-sharing and use agreements 5,9 consistent with the International Committee of Medical Journal Editors authorship guidelines. 28 The importance of security, ease of use, and data validation checks for data quality have been reported previously and have been addressed successfully in existing electronic data-sharing systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Harmonization of imaging, phenotypic, and outcome data to enable data sharing and queries across platforms so that they can be federated by using tools such as Mica-Opal (http://wiki.obiba.org/pages/viewpage.action?pageIdϭ22544438) will be an important step toward encouraging the use of such data bases for TBI imaging research purposes. Furthermore, federation of data bases and data pooling will be greatly facilitated through the systematic use of the National Institute of Neurologic Disorders and Stroke Common Data Elements, [44][45][46][47] which have been developed by more than 200 scientific experts and include more than 1000 CDEs for TBI and another 8000 for other neurologic disorders (http://www.commondataelements.ninds.nih. gov/tbi.aspx#tabϭData_Standards).…”
Section: Unrestrictedmentioning
confidence: 99%